Calpastatin inhibits motor neuron death and increases survival of hSOD1(G93A) mice - Rao, Mala V (J Neurochem, 2016)
Amyotrophic lateral sclerosis (ALS) is a progressive motor neuron disease with a poorly understood cause and no effective treatment. Given that calpains mediate neurodegeneration in other pathological states and are abnormally activated in ALS, we investigated the possible ameliorative effects of inhibiting calpain overactivation in hSOD1(G93A) transgenic (Tg) mice in vivo by neuron specific overexpression of calpastatin (CAST), the highly selective endogenous inhibitor of calpains. Our data indicate that overexpression of CAST in hSOD1(G93A) mice, which lowered calpain activation to levels comparable to WT mice, inhibited the abnormal breakdown of cytoskeletal proteins (spectrin, MAP2 and neurofilaments), and ameliorated motor axon loss. Disease onset in hSOD1(G93A)/CAST mice compared to littermate hSOD1(G93A) mice is delayed, which accounts for their longer time of survival. We also find that neuronal overexpression of CAST in hSOD1(G93A) transgenic mice inhibited production of putative neurotoxic caspase-cleaved tau and activation of Cdk5, which have been implicated in neurodegeneration in ALS models, and also reduced the formation of SOD1 oligomers. Our data indicate that inhibition of calpain with CAST is neuroprotective in an ALS mouse model.